(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article deals with the general nature of the precedent names in the information texts on the TV. Authors of the article distinguishes them into special groups, giving examples of common usage of individual names in information programs. According to the authors, the common usage of some common names in the Kazakh language can be used not only for the purpose of adding styles, but also for the purpose of winning time. The information provided by the use of known names serves to provide a clearer idea of what is being said. The authors conclude that any single names can not be a precedent name. The time has come for the names of names to be preceded.